The Effect of Internal and External Environments on Partnership Strategy and Its Impact on Business Performance of Micro Small Industry of Food Sub-Category in Majalengka Regency - Imma Ismaniar (Politeknik Mardira Indonesia, 2024)
The Industry Food Sub-category is the industry with the largest number of SMEs in Majalengka Regency, and the growth is also high. However, this is not accompanied by the performance of the industry. One of the causes of the decline in the amount of production is due to the limitations of industry business people to market their products. There is a difference in this study with previous research, where there is a significant influence between partnerships and industry performance. The purpose of this study was to determine the description of Internal and External Environments, Partnership Strategies and Business Performance in Food SMIs, and the effect of each independent variable on the dependent variable, both indirectly through an intervening variable and directly through variables. The approach used in this study is a quantitative method. For each variable, there is an effect of each independent variable on the dependent variable, both indirectly through the intervening variable and directly. Internal and External Environment had an influence of 58.02% on the Partnership Strategy, while on Business Performance the influence was 31.28%. The influence of Internal and External Circumstances on Business Performance through the Partnership Strategy on Food SMIs in Majalengka Regency was 9.55%.